THE EFFECT OF CORPORATE GOVERNANCE ON THE VALUE OF PROPERTY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2016-2020 - Rustandi, Herman; Rasiman; Juliansah, Irvan; Kismanah, Imas (prodima@fe.uika-bogor.ac.id, 2026)
The purpose of this study is to investigate the influence of corporate governance on the value of property sector companies listed on the Indonesia Stock Exchange for the period 2016-2020. Exogenous variables including corporate governance are measured by five indicators, including: the size of the board of commissioners, the size of the board of directors, the ownership of managerial shares, the ownership of institutional shares, and the proportion of the independent board of commissioners. Endogenous variables include company value measured by price to book value. The data source is obtained from the official website of the Indonesian stock exchange, namely www.idx.co.id. The population in this study was 83 companies and the research sample was 11 companies consisting of companies in the property, real estate and building construction subsectors. The sampling technique uses the purposive sampling technique that exists in non-probability sampling. The data analysis technique used is structural equation modelling partial least square (SEM-PLS). The results of the study show that corporate governance has a negative and significant effect on the Company's value.